Analysis of Industrial Revolution 4.0 Technology-Based Learning in Higher Education - Mesterjon Mesterjon; Suwarni Suwarni; Diah Selviani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to obtain an overview of the implementation of industrial revolution 4.0 technology-based learning management to improve university learning management, particularly in Bengkulu. The research method used was descriptive qualitative. According to the study's findings, Dehasen University of Bengkulu, Muhammadiyah University of Bengkulu, and Hazairin University of Bengkulu all have access to ICT network infrastructure. As a result, 84% of students and members of the academic community can easily find ICT tools for learning, 83% can easily learn how to use ICT tools for learning on campus, 87% can understand when and how to use ICT tools to achieve specific learning objectives, and 73% have s. This ease of using and accessing SIAKAD, e-learning, and an electronic library